2019
DOI: 10.7759/cureus.6427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pharmacological Agents Administered for Attenuating the Extubation Response on the Quality of Extubation: A Systematic Review

Abstract: Background Several drugs have been tried to obtund the hemodynamic extubation response but all have variable side effects that may affect the quality of short-term recovery. Objective Our primary objective was to evaluate the effect of pharmacological agents, such as dexmedetomidine, local anesthetics, and so on, administered for attenuating the extubation response on the quality of extubation, as judged by the presence or absence of cough, sedation, and laryngospasm/bronchospasm in adult patients who had unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Our study showed that the compound Lidocaine cream also can signi cantly reduce the incident of cough caused by endotracheal extubation about 35% compared NS control group, but there are still 61% patients who have a cough response, perhaps this is because younger patients were more responsive to tracheal tube stimulation of the airway mucosa than older patients [20]. A review study also showed that local anesthetics did not attenuate cough associated with extubation [21], but another eta-study showed that topical airway anesthesia demonstrated better than placebo or no medication in reducing immediate post-extubation cough/bucking [22]. It is well known that tetracaine has a very strong mucosal penetration and can play a better mucosal surface anesthesia [7].…”
Section: Discussionmentioning
confidence: 60%
“…Our study showed that the compound Lidocaine cream also can signi cantly reduce the incident of cough caused by endotracheal extubation about 35% compared NS control group, but there are still 61% patients who have a cough response, perhaps this is because younger patients were more responsive to tracheal tube stimulation of the airway mucosa than older patients [20]. A review study also showed that local anesthetics did not attenuate cough associated with extubation [21], but another eta-study showed that topical airway anesthesia demonstrated better than placebo or no medication in reducing immediate post-extubation cough/bucking [22]. It is well known that tetracaine has a very strong mucosal penetration and can play a better mucosal surface anesthesia [7].…”
Section: Discussionmentioning
confidence: 60%
“…22,23 As extubation itself can also be physically stressful, increasing BP and HR, consideration should be given to smooth extubation by preventing airway irritation and cough in addition to pain control for gentle recovery from anesthesia. [29][30][31] Several options have been introduced for this, including deep extubation, exchanging the endotracheal tube to a laryngeal mask airway prior to extubation, and limiting unnecessary stimulation on emergence such as the "No-Touch technique". 30,32,33 Pharmacologic interventions such as intravenous remifentanil, dexmedetomidine, or lidocaine can be added to facilitate these techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It mainly acts on α2 receptors in the spinal cord and locus coeruleus to inhibit neuronal discharge and sympathetic outflow and reduce sympathetic nerve activity, leading to a reduced perioperative stress response and consequent sedative and analgesic effects. 20 When dexmedetomidine enters the body, it binds to α2 receptors, reducing sympathetic tone and strengthening vagus nerve activity, while inhibiting adenylate cyclase activity and adenosine cyclophosphate synthesis, and reducing the influx of calcium ions to the nerves. The release of transmitters thus reduces hyperpolarization of the presynaptic and postsynaptic membranes, thereby contributing to sedation and the anti-stress response.…”
Section: Discussionmentioning
confidence: 99%
“…The release of transmitters thus reduces hyperpolarization of the presynaptic and postsynaptic membranes, thereby contributing to sedation and the anti-stress response. 4 , 20 …”
Section: Discussionmentioning
confidence: 99%